1997
DOI: 10.1002/(sici)1097-0045(19970501)31:2<118::aid-pros7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase in hyperplasia and carcinoma of the human prostate

Abstract: The expression and activity of aromatase was evaluated in 19 individuals with benign prostatic hyperplasia (BPH) and 26 prostatic carcinoma (PC) patients to elucidate the possible biological significance of in situ estrogen production in the development of human prostatic disorders. Marked aromatase immunoreactivity was observed in proliferative stromal cells, especially those around hyperplastic glands in 18 (95%) BPH patients and in stromal cells surrounding carcinomatous glands in 18 (69%) PC patient specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…A number of studies successfully demonstrated aromatase expression in the prostate by RT-PCR as well as its enzymatic activity by biochemical assay [32][33][34][35][36][37]. In contrast, other studies failed to demonstrate the presence or activity of aromatase [38][39][40][41].…”
Section: Aromatase and The Prostatementioning
confidence: 63%
See 2 more Smart Citations
“…A number of studies successfully demonstrated aromatase expression in the prostate by RT-PCR as well as its enzymatic activity by biochemical assay [32][33][34][35][36][37]. In contrast, other studies failed to demonstrate the presence or activity of aromatase [38][39][40][41].…”
Section: Aromatase and The Prostatementioning
confidence: 63%
“…Much like the data examining aromatase in benign tissue, aromatase expression and activity in PCa and the PCa cell lines had been contentious for some time [32][33][34][35][36][37][38][39][40][41]. However, we demonstrated altered aromatase expression in PCa [42].…”
Section: Aromatase and The Prostatementioning
confidence: 99%
See 1 more Smart Citation
“…ERβ is involved in beneficial effects like anti-proliferation, differentiation and apoptosis. The ability of prostate gland to synthesize estrogens from a locally expressed enzyme aromatase adds to the complexity of the situation (Ellem et al, 2004;Hiramatsu et al, 1997). Aromatase plays a very important role in development of hormone dependent or related neoplasms as breast cancer (Simpson et al, 1994).…”
Section: Estrogen Based Therapymentioning
confidence: 91%
“…Zusammenfassend lässt sich sagen, dass diese Veränderungen auf eine erhöhte stromale DHTProduktion über eine verminderte Ratio von AKR1C1:AKR1C2 hinweisen, welche eine 3a-Diol Bildung bevorzugt (durchbrochene rote Linien). 3a-Diol wird anschließend über eine relativ hohe Ratio von RL-HSD:AKR1C2 zu DHT rückkonvertiert [ [44]. Dies hat zur Entwicklung und Anwendung von Anti-Ös-trogenen und besonders Aromataseinhibitoren zur Therapie der BPH/BPE und dem Prostatakarzinom geführt.…”
Section: Endokrine Regulationunclassified